A population viability analysis of serendipity berry (Dioscoreophyllum cumminsii) in a semi-deciduous forest in Nigeria - Obioh (nee G.U. Ahuama), G. I. B.; Isichei, A. O. (Elsevier B.V., 2014)
The search for natural sweeteners has prompted intensive research on plants with sweetening properties. Dioscoreophyllum cumminsii (Stapf) Diels is a dioecious, semelparous annual liana found as a late successional, understorey species in West Ahican semi-deciduous forests. The fruits and subterranean tubers are intensely sweet and are both edible. The sweetening substance in D. cumminsii is a protein (monellin), which is 3000 times as sweet as sugar. Unfortunately, it is one of the threatened plant species in the country because of massive habitat loss and fragmentation. Conservation is now needed as a salvage programme. Population size is a major determinant of extinction risk. This has prompted the application of growth and population dynamics models to viability analysis of wild species. The aim of population viability analysis (WA) is to determine the minimum viable population size (MVP) or area (MVA) of a particular species. In this paper, MVP was estimated for D. cumminsii using genetic models. The models simulated minimum effective population size of 6040individualsha-I in the ratio of 5032 males to 1008 females. This suggests that to retain evolutionary potential, D. cumminsii requires an effective population size of more than the SOCL5000 range considered adequate for many other species.